INTAKE DESIGN FOR INDONESIAN FIGHTER - Rahmawati, Merti
A research about intake design for Indonesian fighter has been done. The fighter characteristic is flight around Mach 2 at altitude 50,000 feet. This fighter has a rectangular intake configuration with dual ramp using external compression. This research objective is to have the intake configuration with maximum pressure recovery. Refer to Military Specification JSSG 2007 for intake that flight around Mach 2, the maximum pressure recovery is given 92.5 pecent. This research is done by an analytical and numerical approach. The analytical result show that the the configuration has the pressure recovery 95.6 percent. The numerical analysis is done by 2D and 3D model using software ANSYS FLUENT. The numerical result for 2D and 3D model shown that the pressure recovery is comply to the JSSG-2007A.